Pazopanib in patients with von Hippel-Lindau disease: a single-arm, single-centre, phase 2 trial. Issue 10 (October 2018) - Jonasch, Eric; McCutcheon, Ian E; Gombos, Dan S; Ahrar, Kamran; Perrier, Nancy D; Liu, Diane; Robichaux, Christine C; Villarreal, Mercedes F; Weldon, Justin A; Woodson, Ashley H; Pilie, Patrick G; Fuller, Gregory N; et al.
Summary: Background: No approved systemic therapy exists for von Hippel-Lindau disease, an autosomal dominant disorder with pleiotropic organ manifestations that include clear cell renal cell carcinomas; retinal, cerebellar, and spinal haemangioblastomas; pheochromocytomas; pancreatic serous cystadenomas; and pancreatic neuroendocrine tumours. We aimed to assess the activity and safety of pazopanib in patients with von Hippel-Lindau disease. Methods: In this non-randomised, single-centre, open-label, phase 2 trial, adult patients with clinical manifestations of von Hippel-Lindau disease were recruited from the University of Texas MD Anderson Cancer Center (Houston, TX, USA) and were treated with pazopanib (800 mg orally daily) for 24 weeks, with an option to continue treatment if desired by the patient and treating physician. Primary endpoints were the proportion of patients who achieved an objective response and safety in the per-protocol population. The objective response was measured for each patient and each lesion type. Radiographic assessments were done at baseline and every 12 weeks throughout the study. Activity and safety were assessed with continuous monitoring and a Bayesian design. This study is registered withClinicalTrials.gov, numberNCT01436227, and is closed to accrual. Findings: Between Jan 18, 2012, and Aug 10, 2016, we screened 37 patients with genetically confirmed or clinical features consistent with von Hippel-Lindau disease, of whom 31 eligible patients were treated with pazopanib. The proportion of patients who achieved an objective response was 42% (13 of 31 patients). By lesion sites responses were observed in 31 (52%) of 59 renal cell carcinomas, nine (53%) of 17 pancreatic lesions, and two (4%) of 49 CNS haemangioblastomas. Seven (23%) of 31 patients chose to stay on the treatment after 24 weeks. Four (13%) of 31 patients withdrew from the study because of grade 3 or 4 transaminitis, and three (10%) discontinued study treatment because of treatment intolerance with multiple intercurrent grade 1–2 toxicities. Treatment-related serious adverse events included one case each of appendicitis and gastritis and one patient had a fatal CNS bleed. Interpretation: Pazopanib was associated with encouraging preliminary activity in von Hippel-Lindau disease, with a side-effect profile consistent with that seen in previous trials. Pazopanib could be considered as a treatment choice for patients with von Hippel-Lindau disease and growing lesions, or to reduce the size of unresectable lesions in these patients. The safety and activity of pazopanib in this setting warrants further investigation. Funding: Novartis Inc and NIH National Cancer Institute core grant.